MANAJEMEN STRATEGI PERUBAHAN DI SMP NEGERI 39 SAMARINDA - Redza Madzkuri, Muhammad; Eka Wardhana, Kautsar (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
Strategic management is needed when facing changes in educational policies and the demands of technological developments. Therefore, schools carry out planning, implementation, mobilization and supervision processes, as well as factors that support the success of strategic change management in schools. A qualitative descriptive approach was used with a case study approach, with data collection techniques through interviews, observations and documents. The research results show that SMP Negeri 39 Samarinda has carried out a planning strategy based on SWOT analysis to identify needs for change, such as implementing the Independent Curriculum, increasing teacher competency, and developing technological infrastructure. The changes were implemented in stages, starting with socialization and teacher training, followed by the application of project-based learning and hybrid learning methods. However, the change process faces challenges such as teacher resistance, limited technological facilities, and budget constraints. However, the success of change management is supported by the principal’s strong leadership, active participation of the school committee and parents, and regular monitoring and evaluation. This research concludes that the changes in management strategy at SMP Negeri 39 Samarinda are quite effective, requiring continuous adjustments and improvements. The school is expected to continue to adapt and innovate to improve the quality of education and face future challenges optimally.